1987
DOI: 10.2105/ajph.77.5.634
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes education and peer support upon weight and glycemic control of elderly persons with noninsulin dependent diabetes mellitus (NIDDM).

Abstract: We assessed diabetes education and peer support interventions as facilitators of weight loss and glycemic control in a community sample of 79 elderly persons with noninsulin-dependent diabetes mellitus (NIDDM). Different groups received: education only, education and peer support, and no treatment. Peer support was higher in groups where it was actively facilitated. Weight loss and reduction in level of glycemic control occurred within groups receiving both diabetes education and peer support. (Am J Public He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 11 publications
3
49
0
Order By: Relevance
“…Generalizability is likely limited to clinic settings because only four interventions were delivered outside the clinic: three in the home (56,73,75) and one in senior centers (46,63). Interventions focused mainly on lifestyle modification (diet and physical activity) and knowledge levels, with only one study (68) focusing exclusively on skills such as self-monitoring of blood glucose and none using coping skills as the only focus of the intervention.…”
Section: Meta-regressionmentioning
confidence: 99%
“…Generalizability is likely limited to clinic settings because only four interventions were delivered outside the clinic: three in the home (56,73,75) and one in senior centers (46,63). Interventions focused mainly on lifestyle modification (diet and physical activity) and knowledge levels, with only one study (68) focusing exclusively on skills such as self-monitoring of blood glucose and none using coping skills as the only focus of the intervention.…”
Section: Meta-regressionmentioning
confidence: 99%
“…Studies have linked social support to higher health status levels (Wierenga, 1994;Wilson & Pratt, 1987), better compliance with treatment regimen (MacLean & Lo, 1998;Whittemore, Melkus, & Grey, 2005), adherence to self-care activities (Wang & Fenske, 1996;Whittemore et al, 2005), increased health related quality of life (Aalto, Uutela, & Aro, 1997), and improved psychosocial adaptation (Fisher, Lagreca, Creco, Arfken, & Schneiderman, 1997;Karlsen, Idsoe, Hanestad, Murberg, & Bru, 2004;White et al, 1992;Whittemore et al, 2005).…”
Section: Self-regulation Behaviormentioning
confidence: 99%
“…Research on the peer approach in other chronically ill populations has suggested that both the peers providing the support and the patients receiving the support experience benefits (Hamilton & Borstein, 1979;Whittemore et al, 2000;Wilson & Pratt, 1987;Antonucci & Israel, 1986). Most peer support research in the area of HIV has been limited to HIVnegative volunteers who have provided social support to HIV-positive individuals.…”
mentioning
confidence: 99%